2014
DOI: 10.1371/journal.pone.0107658
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dietary Omega-6 to Omega-3 Fatty Acid Ratio and 12/15-Lipoxygenase Deficiency Are Protective against Chronic High Fat Diet-Induced Steatohepatitis

Abstract: Obesity is associated with metabolic perturbations including liver and adipose tissue inflammation, insulin resistance, and type 2 diabetes. Omega-6 fatty acids (ω6) promote and omega-3 fatty acids (ω3) reduce inflammation as they can be metabolized to pro- and anti-inflammatory eicosanoids, respectively. 12/15-lipoxygenase (12/15-LO) enzymatically produces some of these metabolites and is induced by high fat (HF) diet. We investigated the effects of altering dietary ω6/ω3 ratio and 12/15-LO deficiency on HF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…40 However, in this study, we found that the pro-inflammatory Alox15 products 12-HETE and 15-HETE, were not upregulated after CL treatment, suggesting that the pro-inflammatory role of Alox15 is induced by high-fat diet feeding, but not by β -adrenergic stimulation. Thus, key factors that may regulate this dual role of Alox15 include diet, 41 and lipid metabolites generated by the enzyme. 37 Further investigation of Alox15 function in adipose tissue biology is needed in the context of adipose tissue remodeling, including chronic effects of defects in efferocytosis of apoptotic adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, in this study, we found that the pro-inflammatory Alox15 products 12-HETE and 15-HETE, were not upregulated after CL treatment, suggesting that the pro-inflammatory role of Alox15 is induced by high-fat diet feeding, but not by β -adrenergic stimulation. Thus, key factors that may regulate this dual role of Alox15 include diet, 41 and lipid metabolites generated by the enzyme. 37 Further investigation of Alox15 function in adipose tissue biology is needed in the context of adipose tissue remodeling, including chronic effects of defects in efferocytosis of apoptotic adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Neither TNFα nor cholesterol alone enhanced actinomycin D-stimulated caspase 3 activity significantly. However, if mouse hepatocytes were exposed to a combination of TNFα and cholesterol, the actinomycin D-dependent caspase 3 activity was significantly increased about two-fold ( Figure 6C) and there was a significant interaction between cholesterol and TNFα (two-way analysis of variance, obesogenic, diabetogenic and proinflammatory than fat sources such as lard or coconut oil with saturated fatty acids or fish oil with a different PUFA composition (13,14,(37)(38)(39). The high content of n-6-PUFA in soybean oil exaggerated insulin resistance and increased liver steatosis and inflammation in mice (38,14), while a high n-3/n-6-PUFA ratio in the diet reduced hepatic steatosis in humans and mice (39)(40)(41).…”
Section: Main Findingsmentioning
confidence: 99%
“…n-6-fatty acids can be metabolized to arachidonic acid derivatives such as prostanoids (2-series) with proinflammatory properties, whereas n-3-fatty acids serve as substrates for less inflammatory prostanoids (3-and 5-series) or antiinflammatory metabolites (38,42). Serum levels of oxidized metabolites of the n-6 fatty arachidonic and linoleic acids were increased in mice fed a soybean oil-rich high-fat diet compared with mice fed a fish oil-rich high-fat diet (37). Furthermore, oxidized LDL caused Kupffer cell activation in a transgenic mouse model and thus might trigger hepatic inflammation (43).…”
Section: Main Findingsmentioning
confidence: 99%
“…Also, in the Apoe −/− mouse, 5-LOX deficiency protected mice from macrophage infiltration in the liver with decreased hepatic expression of pro-inflammation cytokines (IL-18 and MCP-1) (Martínez-Clemente, Clària, & Titos, 2011). Along similar lines, whole-body genetic knockout of Alox15 in HFD-fed mice resulted in decreased hepatic steatosis, decreased macrophage infiltration, decreased mRNA expression levels of proinflammatory cytokine genes in the liver (IFN-γ, TNF-α and IL-10), and decreased immune cell chemoattractants (Cxcl2/3) (Lazic et al, 2014b). The liver includes multiple different cell types such as hepatocytes, cholangiocytes, Kupffer cells and stellate cells.…”
Section: Nafld Pathogenesismentioning
confidence: 90%
“…Both 12-LOX and 5-LOX are expressed in normal mouse hepatocytes and upon liver damage via acetaminophen the transcript and expression levels of both are increased (Suciu et al, 2016). Likewise, upon HFD-feeding, 12-HETE and 5-HETE is increased compared chow-fed control mice (Lazic et al, 2014a). 5-LOX has been shown to be elevated in the liver of ob/ob mice and 5-LOX inhibition downregulated genes involved in hepatic fatty acid uptake and acyl-CoA oxidase expression, restored hepatic microsomal triglyceride transfer protein activity and hepatic VLDL-triglyceride and Apo-B secretion, suggesting a steatogenic role of 5-LOX.…”
Section: Nafld Pathogenesismentioning
confidence: 99%